- Verbal violence against adolescent students A field study applied to a sample of post-primary students in Muscat Governorate schools - Sultanate of Oman - Ghailani, Salem Mohammed Ali (Journal of Educational and Psychological Sciences, 2020)
The problem of the current study is the study of the issue of linguistic violence against children in the school environment and society. The current study aimed to identify the reality of violence in the language and its level in the community (family) and that the violence directed by the parent, and in the educational environment and intended to violence directed by the teacher. The study also aimed at identifying the level of violence and its relation to some independent variables such as: age, gender, class, the practical situation of the guardian, the educational level of the guardian, the achievement level of the student. The current study belongs to the descriptive studies model, which is based on the descriptive approach, which is actually applied through the social survey method in the sample, for a random sample of 11th and 12th grade students in post-primary education schools in the governorate of Muscat in Oman. The study was based on a basic data collection tool that included two measures: The first was to measure the level of verbal violence directed by parents (fathers and mothers and those who represent a part of the society) towards male and female students in post-primary education, 10 and 12), while the second measure was measured by measuring the level of verbal violence directed by the teacher representing foreigners from the school environment towards the same students. The researcher designed the scale himself, adopting the design and method of Likert Scale. Each scale may be of (29) words. Study limits and areas: The human field: The human field is in the students of the post-primary education schools in Muscat Governorate. The geographical area: Muscat Governorate is a spatial area of ​​this study. The time period is the period in which the registration began from the month of March of 2015 and the data was collected during the period from 1/4/2017 to 5/5/2017. Analytical Methods and Statistical Processes Analysis Techniques: The researcher relied on both qualitative and quantitative analysis methods and according to the design of this study and in line with its objectives and questions and the corresponding hypotheses. Based on the scientific method used in the descriptive approach and the type and nature of field data, Collect, validate, encode, create a database, then unpack and analyze it by relying on the Statistical Package for Social Silences to access valuable indicators and indicators that support the study. Iterative tables simple and composite measures of central tendency, especially arithmetic means, and standard measures of dispersion Calanhrav, in addition to making some important analyzes that the researcher saw an image made for a total college or results of the measure, such as the relative strength. The researcher also used advanced statistical measures in his attempt to conduct hypothesis tests. He relied on the T-Test for independent samples, the ANOVA test and the Person Correlation factor. The study found several important results that confirmed the existence of violence practices The results showed that the level of language violence practiced in the educational environment by teachers is significantly higher than the language violence practiced by parents. The results also indicate that the level of verbal violence practiced against students Higher than the linguistic violence against female students, whether in school or in the community. One of the most important findings is the relationship between the level of language violence and the level of student achievement. The lower the level of student achievement, the higher the level of language violence practiced by both parents and teachers. Thus, the following relationship can be inferred that the lower the level of student achievement, the higher the level of language violence practiced by both the guardian and the teacher. In the end, the study presented some recommendations concerning raising the level of awareness of the family environment (the guardian) and the educational environment (teacher) about the negative effects that language violence can have on students and children at this important age. Some mechanisms to implement the proposed recommendations.
Keywords: linguistic violence; family environment; educational environment; adolescent; post-basic education stage; Sultanate of Oman